Identication of Types and Characteristics of Hazardous Waste at Campus X - Bela Pitaloka; Musarofa; Yuvita Dian Siswanti; Rusdiana Setyaningtyas; Winda Islamiyah Umarie (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Hazardous and toxic waste (B3 waste) management in higher education environments isimportant to prevent environmental pollution and health risks caused by improper wastehandling. Campus operational activities, laboratories, ofces, and facility maintenance activitieshave the potential to generate various types of hazardous waste that require proper managementaccording to environmental regulations. This study aimed to identify the types, characteristics,sources, and generation of B3 waste produced at Campus X. The research used a descriptiveobservational method through direct eld observations, waste generation measurements forseven consecutive days, documentation, and short interviews during the observation process.The results showed that hazardous waste generated at Campus X originated from laboratoryactivities, ofce activities, campus operational activities, and equipment maintenance. Theidentied waste types included electronic waste, used batteries, expired chemicals, infectiouswaste, uorescent lamps, and used hazardous waste packaging. The total hazardous wastegeneration during the observation period reached 57.53 kg with an average generation of 8.22kg/day. Most of the waste characteristics were classied as toxic, corrosive, infectious,ammable, and environmentally hazardous. The study also found that hazardous wastesegregation and temporary storage practices at Campus X were still not fully implementedaccording to technical standards. Therefore, improvements in waste segregation systems,provision of temporary storage facilities, and strengthening of hazardous waste managementpractices are necessary to support environmentally sustainable campus management.